Composition for preparing porous metal structure and three-dimensional phase change heat dissipation porous structure

By using a composition of modified metal particles and an alkenyl group-containing polymer monomer, combined with gel injection molding technology and sintering treatment, the problem of difficulty in preparing a porous metal structure in the prior art is solved, and efficient, uniform and stable preparation of porous metal structures is achieved.

CN119501060APending Publication Date: 2025-02-25SUZHOU CUBRAZING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411657806.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to effectively prepare porous metal structures in the prior art, especially under the demand for high heat flow heat dissipation, traditional methods such as metal mesh-metal powder composite sintering and metal powder loose sintering are difficult to meet the requirements of precision and efficiency.

Method used

A composition is employed, which comprises modified metal particles, an alkenyl group-containing polymer monomer and a crosslinker. Modified metal particles are modified by long-chain compounds and have rich lone pair electron-active groups, improving the compatibility of metal particles with polymerization monomers. The composition is cured in the mold by gel injection molding technology by photocuring or thermal curing, and then subjected to sintering to prepare a porous metal structure.

Benefits of technology

The uniformity and stability of the porous metal structure are achieved, ensuring consistent allotropic shrinkage of the finished parts after sintering, good stability, simple process and strong controllability, and suitable for high heat flow heat dissipation needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501060A_ABST
    Figure CN119501060A_ABST
Patent Text Reader

Abstract

The invention provides a composition for preparing a porous metal structure and a three-dimensional phase change heat dissipation porous structure. The composition comprises modified metal particles, an alkenyl-containing polymer monomer and a cross-linking agent, the modified metal particles comprise metal particles and a long-chain compound modified on the surfaces of the metal particles, the long-chain compound has a structure as shown in the following formula: # imgabs0 #, R1 is at least selected from H, alkyl, aryl or heterocyclic group, R2 is at least selected from H, alkyl, aryl or heterocyclic group, and R3 is at least selected from H, alkyl, aryl or heterocyclic group. R2 is at least selected from an organic group containing N, O, S or P lone electrons, n = 10-500, and m = 1-10. The composition disclosed by the invention is good in stability, a formed green body has relatively good consistency, and a sintered part is consistent in isotropic shrinkage and good in stability. Meanwhile, the preparation of the three-dimensional phase change heat dissipation porous structure can be simply and controllably realized by utilizing the composition and a gel casting process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application specifically relates to a composition for preparing a porous metal structure and a three-dimensional phase-change heat dissipation porous structure, belonging to the field of heat dissipation technology. Background Art

[0002] Porous metal structures are widely used in heat dissipation capillary wicks. The traditional method is metal mesh-metal powder composite sintering and metal powder loose sintering. As the power of the device increases, the thermal management problem becomes increasingly severe. Simple two-dimensional combinations are difficult to meet the needs of high heat flow heat dissipation. At present, various channel thermal design studies continue to emerge, but they generally remain in the experimental stage, and are more simulation calculations. There is an urgent need for a method to simply and efficiently prepare porous heat dissipation materials and prepare metal capillary wick samples for experimental verification. However, 3D printing is costly, the MIM manufacturing process is long, and the mold is expensive, which makes it difficult to meet flexible and changeable development needs and rapid market introduction.

[0003] Gel injection molding is an effective method for preparing three-dimensional ceramic materials developed by Oak Ridge Laboratory in the United States in the 1990s, and has been promoted to a certain extent in the field of dense ceramic parts manufacturing. However, in actual use, this method is difficult to prepare uniform green bodies due to the limited dispersibility of metal powder, monomer and solvent system, which leads to large size differences after sintering and cannot meet the needs of precision scenes. Summary of the invention

[0004] The main purpose of the present application is to provide a composition for preparing a porous metal structure and a three-dimensional phase-change heat dissipation porous structure to overcome the defects of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted in this application includes:

[0006] The first aspect of the present application provides a composition for preparing a porous metal structure, which comprises a metal powder, an olefin-containing polymer monomer and a cross-linking agent; wherein the modified metal particles comprise metal particles and a long-chain compound modified on the surface of the metal particles, and the long-chain compound has a structure shown in the following formula:

[0007]

[0008] Wherein, R1 is at least selected from H, alkyl, aryl or heterocyclic group, R2 is at least selected from organic groups containing N, O, S or P lone electrons, n=10 to 50, m=1 to 10. Exemplarily, R1 can be H, CH3, C2H5, phenyl, CH3CO- or C2H5CO-, etc. Exemplarily, R2 includes amino, hydroxyl, carboxyl, thiol or phosphate, etc.

[0009] Furthermore, the long-chain compound is mainly chemically adsorbed on the empty orbitals of the metal through the abundant lone pairs of electrons contained in its active groups such as amine, hydroxyl, carboxyl, thiol or phosphate groups, and stably modified on the surface of the metal particles.

[0010] In one embodiment, the preparation method of the modified metal particles comprises: at room temperature, uniformly dispersing the metal particles in the solution of the long-chain compound, and continuously stirring for more than 1 hour. The concentration of the solution of the long-chain compound can be 1wt% to 10wt%, preferably 3wt% to 6wt%. The solvent used in the solution of the long-chain compound can be a small molecule alcohol such as methanol, ethanol, isopropanol, or acetonitrile, etc., but is not limited thereto.

[0011] In one embodiment, the composition comprises 50 wt % to 95 wt % of modified metal particles, 5 wt % to 50 wt % of olefin-containing polymer monomers, 0.5 wt % to 20 wt % of a crosslinking agent, 0.1 wt % to 5 wt % of an initiator, and 0 to 30 wt % of a solvent.

[0012] In one embodiment, the mass fraction of the long-chain compound in the modified metal particles is 0.1wt% to 2wt%, preferably 0.5wt% to 1.5wt%. If the ratio is too large, the green strength will be reduced, and conversely, if the ratio is too small, the modification will be insufficient and the performance will be unstable.

[0013] In one embodiment, the particle size of the metal particles is 2 μm to 100 μm, preferably 5 μm to 60 μm. The metal particles have regular or irregular shapes, for example, they may be spherical, coral-shaped, beaded, flake-shaped, columnar, strip-shaped, etc., but are not limited thereto. The material of the metal particles may be one or more of copper, silver, gold, platinum, iron, nickel, cobalt, titanium, etc., but are not limited thereto.

[0014] Furthermore, the content of modified metal particles in the composition is preferably 75 wt% to 95 wt%.

[0015] In the present application, by adjusting the morphology, particle size, etc. of the metal particles, it is possible to control the size and porosity of the porous metal structure prepared from the composition.

[0016] In one embodiment, the long-chain compound includes polyethylene glycol containing at least one or more of a carboxyl group, a thiol group, an amine group, a hydroxyl group or a phosphate group.

[0017] In one embodiment, the alkenyl-containing polymer monomer includes acrylic acid or a derivative thereof, for example, it can be selected from but not limited to one or more of hydroxyethyl methacrylate, acrylamide, methacrylic acid, acrylic acid, methyl methacrylate, ethyl acrylate, butyl acrylate or glycidyl methacrylate.

[0018] Furthermore, the content of the olefin-containing polymer monomer in the composition is preferably 5 wt% to 25 wt%, more preferably 10 wt% to 20 wt%.

[0019] In one embodiment, the crosslinking agent includes an acrylate compound or an alkenylbenzene compound, for example, it can be selected from but not limited to one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, pentaethylene glycol dimethacrylate, N,N-methylenebis(acrylamide) or divinylbenzene.

[0020] Furthermore, the content of the crosslinking agent in the composition is preferably 1 wt% to 10 wt%, more preferably 3 wt% to 5 wt%.

[0021] In one embodiment, the initiator may be selected from benzoyl peroxide, azobisisobutyronitrile or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, etc., but is not limited thereto.

[0022] Furthermore, the content of the initiator in the composition is preferably 0.5 wt% to 2 wt%, more preferably 0.6 wt% to 1.2 wt%.

[0023] In one embodiment, the solvent may be selected from alcohol solvents such as 1,2-propylene glycol, hydrocarbon solvents such as octane, ether solvents such as propylene glycol dimethyl ether, ketone solvents such as 3-pentanone, but is not limited thereto.

[0024] Furthermore, the solvent content in the composition is preferably 3 wt% to 15 wt%, more preferably 3 wt% to 10 wt%.

[0025] The second aspect of the present application provides a method for preparing a porous metal structure by gel casting, which comprises:

[0026] The composition for preparing a porous metal structure is cured in a mold at least by light curing or heat curing to prepare a green body;

[0027] The green compact is sintered to obtain a porous metal structure.

[0028] In one embodiment, the photocuring method includes irradiating the composition filled in the mold with ultraviolet light.

[0029] In one embodiment, the heating temperature used in the thermal curing method is 50°C to 150°C.

[0030] In one embodiment, the sintering process is performed in a protective atmosphere at a temperature of 650° C. to 980° C. for more than 30 minutes, wherein the protective atmosphere includes but is not limited to an atmosphere formed by one or more inert gases such as nitrogen and argon.

[0031] Preferably, the sintering treatment is carried out by programmed temperature rising, and the specific operation includes: in a protective atmosphere, first heating to 300-600°C at a heating rate of 1-10°C / min and maintaining for 30-300min, then heating to 650-980°C at a heating rate of 1-10°C / min and maintaining for 30-300min.

[0032] The third aspect of the present application provides a method for preparing a three-dimensional phase-change heat dissipation porous structure, which specifically includes:

[0033] Filling the composition for preparing a porous metal structure into a three-dimensional mold, and curing the composition by heating or irradiating with light of a set wavelength to obtain a green body;

[0034] In a protective atmosphere, the material is first heated to 300-600°C at a heating rate of 1-10°C / min and maintained for 30-300 min, and then heated to 650-980°C at a heating rate of 1-10°C / min and maintained for 30-300 min to obtain a three-dimensional phase change heat dissipation porous structure.

[0035] In one embodiment, the composition may be cured by heating it to 50-150°C.

[0036] In one embodiment, the light of the set wavelength includes but is not limited to ultraviolet light or visible light, etc., preferably ultraviolet light.

[0037] The fourth aspect of the present application provides a three-dimensional phase-change heat dissipation porous structure, which is prepared by the preparation method of the three-dimensional phase-change heat dissipation porous structure.

[0038] Compared with the prior art, this application has at least the following beneficial effects:

[0039] (1) The present application modifies the surface of metal particles by using the coordination effect of long-chain compounds containing lone-pair electron active group structures in the molecular chain and the empty orbitals of metals, and applies the modified metal particles to acrylic ester organic systems, especially hydroxy acrylic ester organic systems, which can effectively improve the compatibility of metal particles with polymerization reaction monomers and enhance their dispersibility in the composition, so that the composition has good stability. Moreover, when the composition is cured, a gelation reaction can occur uniformly around the metal powder, thereby making the formed green body have good consistency, and the sintered product has consistent shrinkage in all directions and good stability.

[0040] (2) In the present application, by adjusting the morphology and particle size of the metal particles in the composition, the size and porosity of the porous metal structure of the target product can be conveniently adjusted, and the process is simple and controllable.

[0041] (3) The composition described in the present application adopts an acrylate organic system, especially a hydroxy acrylate organic system, which can be formed by heat and light curing, has low equipment requirements, is easy to implement, and has low requirements for molds. For example, a variety of materials such as PP, PC, silicone, and ceramics can be applied. In addition, the composition described in the present application has good biosafety and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 is a scanning electron microscope photograph of the copper powder raw material in Example 1;

[0044] Figure 2 is a photograph of the porous copper core structure of various specifications in Example 1;

[0045] Figure 3 is a scanning electron microscope photograph of the copper powder raw material in Example 2;

[0046] Figure 4 is a photograph of a porous copper core structure in Example 2;

[0047] Figure 5 is a scanning electron microscope photograph of the copper powder raw material in Example 3;

[0048] Figure 6 is a photograph of a porous copper core structure in Example 3;

[0049] Figure 7 yes Figure 6 A partial magnified photo of the porous copper core structure shown;

[0050] Figure 8 is a scanning electron microscope photograph of the copper powder raw material in Example 4;

[0051] Fig. 9 is a scanning electron microscope photograph of a transverse cross section of a porous copper core structure in Example 4;

[0052] Fig.10 yes Fig. 9 A partial enlarged photograph of the porous copper core structure shown. DETAILED DESCRIPTION

[0053] In order to fully understand the purpose, technical content and features of this application, the technical solution of this application will be further described in detail below in conjunction with several embodiments. However, the implementation of this application is not limited to these specific details, and can also be implemented in other ways different from those described herein. Therefore, the specific embodiments presented in this application are only examples and not limitations.

[0054] Example 1 A method for preparing a porous copper core structure by gel casting comprises the following steps:

[0055] S1. At room temperature, the copper powder raw material (Suzhou Tongbaorui New Materials Co., Ltd., trade name SR-2) was evenly dispersed in an ethanol solution of PEG-NH2 (Sinopharm Chemical Reagent Co., Ltd., molecular weight 5k) with a concentration of about 5wt%, and the stirring was continued for about 1 hour. After that, the copper powder was filtered out and dried at about 50°C for about 6 hours to obtain modified copper powder.

[0056] S2, about 14g of hydroxyethyl methacrylate, about 8g of ethylene glycol dimethacrylate and about 8g of 1,2-propylene glycol were uniformly mixed, and about 210g of the modified copper powder was added and stirred evenly, and about 2g of benzoyl peroxide was added and stirred evenly to form a composition. The composition had no obvious sedimentation phenomenon after standing at room temperature for 7 days.

[0057] S3, filling the freshly prepared composition into a three-dimensional mold made of silica gel, placing it in an oven at about 80° C. and heating it for about 30 minutes to obtain a green body, and then removing the green body from the mold.

[0058] S4. Sintering the green body in a nitrogen sintering furnace. The specific sintering procedure is: first heating to about 300°C at a heating rate of about 2°C / min, maintaining for about 60 minutes, then heating to about 450°C at a heating rate of about 3°C / min, maintaining for about 60 minutes, and then heating to about 800°C at a heating rate of about 3°C / min, maintaining for about 60 minutes, to obtain a porous copper core structure with a porosity of about 45%.

[0059] Figure 1 An optical photograph of the copper powder raw material is shown (magnification 1000), in which the copper particles are substantially spherical. Figure 2 The porous copper core structures of various specifications obtained after forming and sintering in this embodiment are shown, all of which are three-dimensional porous copper core materials with planar convex points combined. It can be seen that the green body prepared in this embodiment has good consistency, and the finished product shrinks in all directions after sintering, and has high stability.

[0060] Comparative Example 1 The method for preparing a porous copper core structure provided in this comparative example is basically the same as that in Example 1, except that PEG-NH2 is replaced by octadecylamine in step S1. The composition in this comparative example shows obvious sedimentation after being left at room temperature for 2 days.

[0061] Comparative Example 2 The method for preparing a porous copper core structure provided in this comparative example is basically the same as that in Example 1, except that PEG-NH2 is replaced with PEG of the same molecular weight in step S1. The composition in this comparative example shows obvious sedimentation after standing at room temperature for 1 day.

[0062] Comparative Example 3 The method for preparing a porous copper core structure provided in this comparative example is basically the same as that in Example 1, except that PEG-NH2 is replaced by triethanolamine in step S1. The composition in this comparative example shows obvious sedimentation after being left at room temperature for 10 minutes.

[0063] Comparative Example 4 The method for preparing a porous copper core structure provided in this comparative example is basically the same as that in Example 1, except that step S1 is omitted, and the modified copper powder is replaced by the copper powder raw material in step S2. The composition in this comparative example shows obvious sedimentation after standing at room temperature for 10 minutes.

[0064] Comparative Example 5 The method for preparing a porous copper core structure provided in this comparative example is basically the same as that in Example 1, except that 2 g of ethylene glycol dimethacrylate is used instead of hydroxyethyl methacrylate in step S2. The composition in this comparative example shows obvious sedimentation after standing at room temperature for 6 days.

[0065] Example 2 A method for preparing a porous copper core structure by gel casting comprises the following steps:

[0066] S1. At room temperature, the copper powder raw material (Suzhou Tongbaorui New Materials Co., Ltd., trade name R-325) was evenly dispersed in an ethanol solution of PEG-COOH (Sinopharm Chemical Reagent Co., Ltd., molecular weight 6k) with a concentration of about 3wt%, and the stirring was continued for about 1 hour. After that, the copper powder was filtered out and dried at about 50°C for about 6 hours to obtain modified copper powder.

[0067] S2, about 48g acrylamide, about 14g N, N-methylenebis (acrylamide) and about 10g propylene glycol dimethyl ether were uniformly mixed, and then about 210g of the above-mentioned modified copper powder was added and stirred evenly, and then about 2g of azobisisobutyronitrile was added and stirred evenly to form a composition. The composition was left standing at room temperature for 7d without obvious sedimentation.

[0068] S3, filling the freshly prepared composition into a three-dimensional mold made of PC material, placing it in an oven at about 70° C. and heating it for about 30 minutes to obtain a green body, and then removing the green body from the mold.

[0069] S4. Sintering the green body in a nitrogen sintering furnace. The specific sintering procedure is: first heating to about 300°C at a heating rate of about 1°C / min, maintaining for about 300 minutes, then heating to about 600°C at a heating rate of about 3°C / min, maintaining for about 60 minutes, and then heating to about 900°C at a heating rate of about 10°C / min, maintaining for about 30 minutes, to obtain a porous copper core structure.

[0070] Figure 3 An optical photograph of the copper powder raw material is shown (magnification 500), in which the copper particles are substantially spherical particles. Figure 4 The three-dimensional porous copper material after forming and sintering is shown. It can be seen that the porous copper core structure prepared in this embodiment has consistent shrinkage in all directions and high stability.

[0071] Example 3 A method for preparing a porous copper core structure by gel casting comprises the following steps:

[0072] S1. At room temperature, the copper powder raw material (Suzhou Tongbaorui New Materials Co., Ltd., trade name TL-325) was evenly dispersed in an ethanol solution of PEG-SH (Sinopharm Group Chemical Reagent Co., Ltd., molecular weight 2k) with a concentration of about 6wt%, and the stirring was continued for about 1 hour. After that, the copper powder was filtered out and dried at about 50°C for about 6 hours to obtain modified copper powder.

[0073] S2, about 25g of methyl methacrylate, about 10g of tetraethylene glycol dimethacrylate and about 8g of octane were uniformly mixed, and about 155g of the modified copper powder was added and stirred evenly, and about 2g of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was added and stirred evenly to form a composition. The composition was left standing at room temperature for 7 days without obvious sedimentation.

[0074] S3, filling the freshly prepared composition into a three-dimensional mold made of PC material, placing it under UV light for curing for about 30 minutes to obtain a green body, and then removing the green body from the mold.

[0075] S4. Sintering the green body in a nitrogen sintering furnace. The specific sintering procedure is: first heating to about 300°C at a heating rate of about 2°C / min, maintaining for about 60 minutes, then heating to about 450°C at a heating rate of about 2°C / min, maintaining for about 60 minutes, and then heating to about 700°C at a heating rate of about 5°C / min, maintaining for about 300 minutes, to obtain a porous copper core structure with a porosity of about 45%.

[0076] Figure 5 An optical photograph of the copper powder raw material is shown (magnification 500), wherein the copper particles therein are substantially irregularly shaped particles. Figure 6 and Figure 7 The porous copper core structure obtained after forming and sintering in this embodiment is shown, which is a three-dimensional porous copper material with a long strip shape and grooves. It can be seen that the porous copper core structure prepared in this embodiment has consistent shrinkage in all directions and high stability.

[0077] Example 4 A method for preparing a porous copper core structure by gel casting comprises the following steps:

[0078] S1. At room temperature, the copper powder raw material (Suzhou Tongbaorui New Materials Co., Ltd., trade name UL-325) was evenly dispersed in an ethanol solution of PEG-SH (Sinopharm Group Chemical Reagent Co., Ltd., molecular weight 2k) with a concentration of about 5wt%, and the stirring was continued for about 1 hour. After that, the copper powder was filtered out and dried at about 50°C for about 6 hours to obtain modified copper powder.

[0079] S2, about 20g of methyl methacrylate, about 10g of tetraethylene glycol dimethacrylate and about 15g of 3-pentanone were uniformly mixed, and about 150g of the modified copper powder was added and stirred evenly, and about 2g of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was added and stirred evenly to form a composition. The composition had no obvious sedimentation phenomenon after standing at room temperature for 7 days.

[0080] S3. Fill the freshly prepared composition into a three-dimensional mold made of PP material, place it under a xenon lamp ultraviolet light source at 365 nm for continuous irradiation for about 30 minutes to obtain a green body, and then remove the green body from the mold.

[0081] S4. Sintering the green body in a nitrogen sintering furnace. The specific sintering procedure is: first heating to about 300°C at a heating rate of about 2°C / min, maintaining for about 60 minutes, then heating to about 450°C at a heating rate of about 2°C / min, maintaining for about 60 minutes, and then heating to about 800°C at a heating rate of about 3°C / min, maintaining for about 60 minutes, to obtain a porous copper core structure with a porosity of about 45%.

[0082] Figure 8An optical photograph of the copper powder raw material is shown (magnification 1000), wherein the copper particles are substantially coral-like particles. Fig. 9 and Fig.10 A porous copper core structure obtained after forming and sintering in this embodiment is shown respectively, which is a long strip of three-dimensional porous copper material containing grooves. It can be seen that the porous copper core structure prepared in this embodiment has consistent shrinkage in all directions and high stability.

[0083] A series of absorbent cores for temperature equalizing plates of the same specifications were prepared according to the methods of Examples 1-4 and Comparative Examples 1-4, and then the absorbent properties and mechanical properties of these absorbent cores were tested according to CN202410836428.3 and GBT 232-2024. The results are shown in Table 1 below.

[0084] Table 1 Performance test results of the liquid absorbent core for the temperature averaging plate prepared in Examples 1 to 4 and Comparative Examples 1 to 5

[0085] Porosity (%) <![CDATA[Permeability × 10 -11 (m 2 )]]> Capillary pressure / kPa Compressive strength / MPa Example 1 35.2 0.58 1.78 34.1 Comparative Example 1 35.6 0.44 1.83 33.4 Comparative Example 2 36.3 0.46 1.46 33.6 Comparative Example 3 34.8 0.34 1.89 32.8 Comparative Example 4 35.1 0.51 1.64 33.1 Comparative Example 5 35.7 0.49 1.59 32.6 Example 2 41.8 0.85 0.89 30.9 Example 3 46.4 1.28 1.98 25.7 Example 4 47.6 1.07 2.34 22.5

[0086] The above embodiments are only intended to illustrate the technical concept and efficacy of the present application, and the purpose is to enable persons familiar with the technical field to understand the content of the present application and implement it accordingly. However, these embodiments do not constitute a limitation on the scope of protection of the present application. Any equivalent transformation or modification made on the premise of the spirit and technical idea of ​​the present application should be covered by the claims of the present application.

Claims

1. A composition for preparing a porous metal structure, comprising metal powder, an olefin-containing polymer monomer and a crosslinking agent; characterized in that: The metal powder includes modified metal particles, and the modified metal particles include metal particles and long-chain compounds modified on the surface of the metal particles, and the long-chain compounds have a structure shown in the following formula: Among them, R1 is at least selected from H, alkyl, aryl or heterocyclic group, R2 is at least selected from organic groups containing N, O, S or P lone electrons, n=10-500, m=1-10.

2. The composition for preparing a porous metal structure according to claim 1, characterized in that: The composition comprises 50 wt % to 95 wt % of modified metal particles, 5 wt % to 50 wt % of olefin-containing polymer monomers, 0.5 wt % to 20 wt % of a crosslinking agent, 0.1 wt % to 5 wt % of an initiator and 0 to 30 wt % of a solvent.

3. The composition for preparing a porous metal structure according to claim 1, characterized in that: The mass fraction of the long-chain compound in the modified metal particles is 0.1% to 2%; and / or the particle size of the metal particles is 2μm to 100μm; and / or the metal particles have a regular shape or an irregular shape; and / or R2 includes an amino group, a hydroxyl group, a carboxyl group, a thiol group or a phosphate group; and / or the olefinic polymer monomer includes acrylic acid or its derivatives; and / or the crosslinking agent includes an acrylate compound or an olefinic benzene compound.

4. The composition for preparing a porous metal structure according to claim 3, characterized in that: The long-chain compound includes polyethylene glycol containing at least one or more of hydroxyl, carboxyl, thiol, amine or phosphate groups; and / or the alkenyl-containing polymer monomer includes one or more of hydroxyethyl methacrylate, acrylamide, methacrylic acid, acrylic acid, methyl methacrylate, ethyl acrylate, butyl acrylate or glycidyl methacrylate; and / or the cross-linking agent includes one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, pentaethylene glycol dimethacrylate, N,N-methylenebis(acrylamide) or divinylbenzene.

5. The composition for preparing a porous metal structure according to claim 2, characterized in that: The solvent includes an alcohol solvent, a hydrocarbon solvent, an ether solvent or a ketone solvent; and / or the initiator includes benzoyl peroxide, azobisisobutyronitrile or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

6. A method for preparing a porous metal structure by gel casting, characterized in that: include: The composition for preparing a porous metal structure according to any one of claims 1 to 5 is cured in a mold by at least photocuring or thermal curing to form a green body; The green compact is sintered to obtain a porous metal structure.

7. The preparation method according to claim 6, characterized in that: The light curing method includes irradiating the composition filled in the mold with ultraviolet light; the heating temperature used in the heat curing method is 50°C to 150°C.

8. The preparation method according to claim 6, characterized in that: The sintering treatment is carried out in a protective atmosphere, the sintering temperature is 650° C. to 980° C., and the time is more than 30 minutes.

9. A method for preparing a three-dimensional phase-change heat dissipation porous structure, characterized in that: Specifically include: Filling the composition for preparing a porous metal structure according to any one of claims 1 to 5 into a three-dimensional mold, and curing the composition by heating or irradiating with light of a set wavelength to obtain a green body; In a protective atmosphere, the material is first heated to 300-600°C at a heating rate of 1-10°C / min and maintained for 30-300 min, and then heated to 650-980°C at a heating rate of 1-10°C / min and maintained for 30-300 min to obtain a three-dimensional phase change heat dissipation porous structure.

10. A three-dimensional phase-change heat dissipation porous structure, characterized in that: It is prepared by the method described in claim 9.

Citation Information

Patent Citations

  • Method and device for testing permeability of capillary structure

    CN118624494A